Ability to Prepare Financial Reports, Financial Literacy and the use of Information Technology on MSME Performance - Yuniar, Fira; Aatriani, Devi; Arimurti, Trias (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
This research was conducted to determine and test the influence of the variables of ability to prepare financial reports, financial literacy and use of information technology on the performance of MSMEs. In order to get conclusions, the researcher applied a quantitative approach. The data type chosen for analysis is primary data. This type was taken through a sampling technique in the form of a questionnaire or survey where the number of respondents used was 100 respondents. The respondents were taken from MSME actors in Karawang Regency. Sampling was carried out by applying special criteria according to the needs of the research being carried out. Conclusions were drawn using statistical methods. After the study was completed, the results or conclusions obtained from the research carried out were in the form of the variable ability to prepare financial reports which had a positive and significant influence or impact on the performance of MSMEs. Not much different, the financial literacy variable or understanding of financial management also has a positive and significant influence or impact on the performance of MSMEs. The variable use of information technology also has a positive and significant impact on MSME performance. Finally, there are variables that ability to prepare financial reports, financial literacy and the use of information technology have a positive and significant effect on the performance of MSMEs.